Training Status as a Marker of the Relationship between Nitric Oxide, Oxidative Stress, and Blood Pressure in Older Adult Women - Jacomini, André Mourão; de Souza, Hugo Celso Dutra; Dias, Danielle da Silva; Brito, Janaina de Oliveira; Pinheiro, Lucas Cezar; da Silva, Anderson Bernardino; da Silva, Roberta Fernanda; Trapé, Atila Alexandre; De Angelis, Kátia; Tanus-Santos, José Eduardo; do Amaral, Sandra Lia; Zago, Anderson Saranz (Wiley, 2015)
The purpose of this study was to evaluate the influence of functional fitness and oxidative capacity on the nitric oxide concentration associated with hemodynamic control in older adult women. The sample consisted of 134 women (65.73 ± 6.14 years old). All subjects underwent a physical examination to assess body mass index, waist-hip ratio, body fat measurement by dual energy X-ray absorptiometry, and blood pressure (BP). Training status (TS) was evaluated by indirect determination of maximal oxygen uptake by a treadmill test using Balke protocol modified for older adults. Functional fitness was also evaluated through a Functional Fitness Battery Test to determine the general fitness functional index (GFFI). All participants were separated according to the functional fitness (TS1, very weak and weak; TS2, regular; TS3, good and very good). Plasma blood samples were used to evaluate prooxidant and antioxidant activity and nitrite and nitrate concentrations. The general results of this study showed that good levels of TS were related to lower levels of lipoperoxidation and protein damage, higher levels of antioxidant, and higher concentration of nitrite and nitrate. This combination may be responsible for the lower levels of BP in subjects with better TS.